Roost Site Selection by Red Knots (Calidris canutus rufa) in Delaware Bay - Zimmerman, Kathryn (2010)
I monitored the roosting preferences of 53 Red Knots (Calidris canutus rufa) during their northbound migratory stopover in Delaware Bay in 2008 and 2009. The goal was to locate the high tide daytime and nighttime roosts as well as to determine the habitat characteristics that create suitable roost sites. Radio-tracking data were used in collaboration with aerial photos to map and locate high tide roost sites. Habitat surveys were used to determine environmental characteristics that correlated with roost site use. Birds preferred shoreline habitat during the day, but preferred inland habitat at night. Birds’ preference for inland roost sites increased significantly at spring tides. The results of this study can inform local resource managers about the restoration and conservation of roost sites in Delaware Bay for shorebirds. Master of Science (MS) Natural Resources and Environment University of Michigan http://deepblue.lib.umich.edu/bitstream/2027.42/78411/1/MS_Thesis-Kathryn Zimmerman-Dec2010.pdf